The Influence of Work Discipline, Work Ethos and Work Environment on Employee Work Achievement: Lessons from Local Organization in an Emerging Country - Javed Octovianus Sipahelut; Anita Erari; Maman Rumanta (Budapest International Research and Critics University, 2021)
The Office of Industry, Trade, Cooperatives and Small and Medium Enterprises of Yapen Islands Regency, Papua, as a local government agency is obliged to foster, protect, and pay attention to issues related to industry, trade, cooperatives, and small and medium enterprises. Good employee performance is important in order to support the smooth running of official duties. This study aims to examine and analyze the effect of work discipline, work ethic and work environment on employee work performance at the Department of Industry, Trade, Cooperatives and Small and Medium Enterprises, Yapen Islands Regency. Data collection techniques were carried out by distributing questionnaires and interviews. The sample used in this study were 66 respondents. The hypothesis was tested by multiple linear regression analysis with the help of SPSS software. The results of the analysis show that work discipline has a significant positive effect on employee work performance, the higher the level of employee discipline, the higher the work performance. Work ethic has a significant positive effect on employee work performance, the better the work ethic of the employee, the better the work performance. The work environment has a significant positive effect on employee work performance, the better the work environment, the better the employee's work performance.